ICE MAKER TOOL DESIGN - Eko Setyo Prabowo; Wiyogo (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2022)
The purpose of this research is to design an ice maker using split AC machine with AutoCAD application software. This study uses a combination research design (mix methods), namely the researcher collect, analyze between quantitative and qualitative data in one study that same. Combination research design aims to complement the description of the results research on the events under study and to strengthen the research analysis. researcher choose to use explanatory which is included in the sequential model (sequence). Design This type is a mixed methods research design carried out by carrying out qualitative research first and then proceed with quantitative research. Based on the results of the design of the ice maker tool using the AutoCAD application 2016 it can be concluded that the size of the ice maker cooling box has a length of 520 mm, 460 mm wide and 520 mm high. The capacity of the number of ice cubes produced in one production process as many as 10 plastic bags of sugar one kilo. Storage box size The cooling water for the ice maker has a length of 370 mm, a width of 280 mm, and a height of 290 mm. The size of the ice maker frame or frame has a length of 1200 mm, a width of 650 mm, and has a height of 50 mm. The Split AC machine used is Split AC PK, the refrigerant that is used is refrigerant R22. Documentation of the design results of the ice maker tool using the AutoCAD application printed on A3 paper. Use accurate measuring tools so that the measurement results are more precise and precise. Research This is hoping for further research, regarding the design of the ice maker in order to obtain information that really becomes a reference for the community in good cooling. Need the existence of learning media that are validated by media experts so that when making tools they can be learning materials.